Politik Media dalam Transisi Politik: Dari Kontrol Negara Menuju Self-Regulation Mechanism - Wahyuni, Hermin Indah (FISIP Universitas Atma Jaya Yogyakarta, 2007)
Abstract: The political transformation in 1998 introduced a new era of Indonesian media which respects the public interest and implements a democratic model. The changing led to a new media-politics that have democratic character. This article will focus on the self regulation mechanism that becomes very popular in democratic mass media system. Those favouring self-regulation mechanism have usually justified it on the grounds that it is less damaging to freedom of expression than legal control. However this mechanism is not a panacea for all ills, because self-regulation can only work if certain pre-conditions are met. The analysis will be done by several conceptual frames, i.e: the concept of media in political transition, concept of media politics, self regulation mechanism, and statutory vs voluntary regulation.